Research on performances of speed regulating mechanism of mine-used permanent magnet speed regulator - WANG Lei; JIA Zhenyuan; ZHU Mingliang; ZHANG Li (Gong-kuang zidonghua, 2018)
Structure and principles of mine-used permanent magnet speed regulator were introduced. A sinusoidal-based speed regulating groove was designed and contact stress of the groove was analyzed by finite element method. Axial force and air gap value in the permanent magnetic speed regulator were fitted by function curve, according to characteristic function curve of the groove, torque values under different air gaps were obtained. Actual output torque of actuator was obtained through test。By comparing theoretical calculation value of torque with the test results, it is found that both have the same change trend and high coincidence degree, peak torque error was 5.5%.Through numerical calculation method of function curve fitting, the value of speed regulation torque under different air gaps is quantified, which can provide technical support for research of speed regulating mechanism of permanent magnet speed regulator.